2017
DOI: 10.1653/024.100.0209
|View full text |Cite
|
Sign up to set email alerts
|

Oviposition ofAnastrepha fraterculusandCeratitis capitata(Diptera: Tephritidae) in Citrus Fruits, and Development in Relation to Maturity of Orange Fruits

Abstract: Fruit flies (Diptera: Tephritidae) are considered to be one of the principal groups of pests in fruit culture worldwide. The objective of this study was to investigate oviposition by Anastrepha fraterculus (Wiedemann) and Ceratitis capitata (Wiedemann) in citrus fruits and to assess the development of these species in relation to the maturity of orange fruits. The experiments were carried out under controlled temperature conditions (25 ± 2 °C), RH (70 ± 10%), and photoperiod (12:12 h L:D). Oviposition was eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The infestation of citrus fruits by C. capitata in the field is influenced by several factors and might not be directly linked to the effects of fruit volatiles on the females' oviposition. Citrus species and variety, maturity stage of the fruits, host availability, population density of the insect, natural enemies, control measures, and environmental conditions of the area are some of the key factors determining the infestation level (Mavritakis et al 2000, Staub et al 2008, Dias et al 2017, Duarte et al 2021). However, the main components conferring partial resistance of citrus fruits to C. capitata infestations are the physicochemical characteristics of citrus peels (Papachristos and Papadopoulos 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The infestation of citrus fruits by C. capitata in the field is influenced by several factors and might not be directly linked to the effects of fruit volatiles on the females' oviposition. Citrus species and variety, maturity stage of the fruits, host availability, population density of the insect, natural enemies, control measures, and environmental conditions of the area are some of the key factors determining the infestation level (Mavritakis et al 2000, Staub et al 2008, Dias et al 2017, Duarte et al 2021). However, the main components conferring partial resistance of citrus fruits to C. capitata infestations are the physicochemical characteristics of citrus peels (Papachristos and Papadopoulos 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Females are hypothesized to prefer ovipositing on plant-hosts that provide an optimal nutritional environment that maximizes survival and performance (Gripenberg et al 2010). Fruits texture, color, shape, and size as well as their chemical characteristics such as nutrients, water content, attractive and repellent substances have an important effect on the selection of the oviposition site (Dias et al 2017). Apart from those physical and chemical properties of the fruit, volatiles organic compounds (VOCs) emitted from host fruits play a decisive role for the selection of the appropriate fruit for oviposition (Papadopoulos et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The infestation indices and pupal viability of A. fraterculus and C. capitata varied between exposure to infestation period and fruit species (as shown in Table 2). of natural enemies, host availability and maturation and oviposition stimuli are relevant (Price et al, 1980;Prokopy and Roitberg, 1984;Vayssières et al, 2009;Bisognin et al, 2015;Dias et al, 2017;Sivinski et al, 2004). Anastrepha fraterculus (Wiedemann, 1830) and Ceratitis capitata (Wiedemann, 1824) are polyphagous and holometabolic insects whose immature stages develop inside fruit.…”
Section: Infestation Bioassaymentioning
confidence: 99%
“…The reproductive success of holometabolous phytophagous insects, such as Mediterranean fruit fly, especially those whose larvae have low mobility, are largely dependent on the resources selected by females via oviposition. Thus, parental traits and decisions, such as the choice of an adequate oviposition site, are critical to offspring survival and success (Yuval et al 2002, Segura et al 2007, Dias et al 2017). Several studies on the host preference and acceptance of C. capitata have been carried out to better understand how females select the proper host for oviposition (Joachim-Bravo and Silva-Neto 2004, Diamantidis et al 2008, Papachristos and Papadopoulos 2009).…”
mentioning
confidence: 99%
“…Several studies on the host preference and acceptance of C. capitata have been carried out to better understand how females select the proper host for oviposition (Joachim-Bravo and Silva-Neto 2004, Diamantidis et al 2008, Papachristos and Papadopoulos 2009). It has been found that a complex balance of plant physical and chemical factors can affect both the final selection of hosts and tephritid larval development (Joachim-Bravo et al 2001, Aluja and Mangan 2008, Papachristos et al 2008, Dias et al 2017). Studies regarding the effect of different larval host on the offspring have been carried out on C. capitata and other polyphagous tephritids.…”
mentioning
confidence: 99%